Exploring a new ultrasound score as a clinical predictive tool in patients with rheumatoid arthritis starting abatacept: results from the APPRAISE study. Issue 1 (5th May 2016) - D'Agostino, Maria-Antonietta; Boers, Maarten; Wakefield, Richard J; Berner Hammer, Hilde; Vittecoq, Olivier; Filippou, Georgios; Balint, Peter; Möller, Ingrid; Iagnocco, Annamaria; Naredo, Esperanza; Østergaard, Mikkel; Gaillez, Corine; et al.
Abstract : Objectives: To explore whether changes in a composite (power Doppler/greyscale ultrasound (PDUS)) synovitis score, developed by the OMERACT-EULAR-Ultrasound Task Force, predict disease activity outcomes in rheumatoid arthritis (RA). Methods: Patients with RA who were methotrexate inadequate responders starting abatacept were evaluated. Individual joint PDUS scores were combined in the Global OMERACT-EULAR Synovitis Score (GLOESS) for metacarpophalangeal joints (MCPs) 2–5, all joints (22 paired) and a reduced (9 paired) joint set. The predictive value of changes in GLOESS at week 1–16 evaluations for clinical status and response (Disease Activity Score (DAS)28 (C reactive protein, CRP) <2.6; DAS28(CRP) ≤3.2; DAS28(CRP) ≥1.2 improvement) up to week 24, and correlations between DAS28 and GLOESS were assessed. Results: Eighty-nine patients completed the 24-week treatment period. Changes in GLOESS (MCPs 2–5) from weeks 1 to 16 were unable to predict DAS28 outcomes up to week 24. However, significant improvements in GLOESS (MCPs 2–5) were observed at week 12 in patients with DAS28 ≥1.2 improvement at week 24 versus those who did not achieve that clinical response. In patients achieving DAS28 ≥1.2 improvement or DAS28 ≤3.2 at week 24, changes in GLOESS (22 and 9 paired joint sets) were greater in patients who already achieved DAS28 ≥1.2 at week 12 than in those who did not. No significant correlations were found between changes in DAS28 and GLOESS definitions at any time point. Conclusions: PDUS was not correlated with clinical status or response as measured by DAS28-derived criteria, and PDUS changes were not predictive of clinical outcome. The discrepancies require further exploration. Trial registration number: NCT00767325; Results.